An investigation on utilization of poly-electrolytes as dispersant for kaolin slurry and its slip casting properties - Eygi, Mustafa Salih; Ateşok, Gündüz (Elsevier BV, 2008)
Abstract The ratio of kaolins in the sanitaryware recipes are considered with their certain slip casting properties such as casting concentration (mass% solid), casting rate and unfired strength. Hence, the first condition is to obtain the stability of their high solid contained slurries which are generally regulated with dispersants such as sodium silicate (Na 2 SiO 3 ) and sodium carbonate (Na 2 CO 3 ). In this study, poly-electrolytes were used as a dispersant for kaolin slurry and their effect on certain slip casting properties of kaolin were investigated. Obtained results were compared to tests with sodium silicate. Results indicated that poly-electrolytes were more effective than sodium silicate to decrease the viscosity of kaolin slurries. Casting concentration of the kaolin slurries and strength of unfired kaolin bodies increased noteworthy amount when using poly-electrolytes instead of sodium silicate. However, casting rate of the slurries decreased with using poly-electrolytes instead of sodium silicate.